Epstein–Barr Virus–Associated Encephalitis in an Immunocompetent Adult: A Case Report From Thailand - Ekachai Singhatiraj; Pavis Laengvejkall; Put Chaikamnerd; Krit Pongpirul (Case Reports in Infectious Diseases, 2025)
We report a case of Epstein-Barr virus (EBV) encephalitis in a 27-year-old man from Bangkok, Thailand, presenting with fever and altered mental status. Cerebrospinal fluid analysis showed neutrophil predominance and EBV-positive PCR. The patient improved with intravenous dexamethasone, highlighting EBV as a potential encephalitis pathogen in immunocompetent individuals.
Keywords: Viral-associated cancers and disorders; CNS Lymphoma Diagnosis and Treatment; Cytomegalovirus and herpesvirus research